PENGARUH KOMITMEN ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Rahmawati, Ade Azzahra; Trisninawati, Trisninawati (Jurnal Keuangan dan Bisnis, 2024)
The main objective of this research is to examine the influence of organizational commitment and work discipline on employee performance with job satisfaction as an intervening variable. The method employed is quantitative, with the employees of the Palembang City Library and Archives Department as the research subjects. The total sampling technique was used with a sample size of 94 respondents, and data collection was conducted using questionnaires. Data analysis was performed using SmartPLS 4. The results of this study indicate that organizational commitment has a positive effect on employee performance, work discipline has a positive effect on employee performance, job satisfaction has a positive effect on employee performance, organizational commitment has a positive effect on job satisfaction, work discipline has a positive effect on job satisfaction, job satisfaction can mediate the relationship between organizational commitment and employee performance, and job satisfaction can mediate the relationship between work discipline and employee performance.